Tradisi Baru Perpustakaan dalam Perannya sebagai Institusi Pengetahuan - Ifonila Yenianti (Pustabiblia: Journal of Library and Information Science, 2018)
Library is not only a place to display books, but there are many important values within. The Library paradigm of book oriented has shifted into user oriented. It means that library becomes a centre of information. On the top of that, library is also transforms into a knowledge institution to serve, illuminate, and make knowledge as a culture. In this technological era, this article presents interesting phenomena in The Libraries of State Institute for Islamic Studies (PTKIN) under The Ministry of Religious Affairs Indonesia about the emergence and the development of new traditions including Online Research Skills (ORS) and Writing Skills (WS)